Peran Keputusan Berkunjung Dalam Meningkatkan Pengaruh Pemasaran Media Sosial Dan Citra Destinasi Terhadap Kepuasan Wisatawan Di Taman Wisata Alam (TWA) Angke Kapuk - Natalia Dea Kurniawati; Nova Eviana (Eduturisma, 2024)
Tourist satisfaction has been extensively discussed in various academic studies owing to its potential to yield managerial benefits while simultaneously upholding the sustainability of tourist destinations. Prior research has yielded varied findings concerning the impact of social media marketing and destination image on tourist satisfaction. Discrepancies in these findings have prompted inquiries into potential mediating variables. This study aims to investigate the direct influence of social media marketing and destination image on tourist satisfaction, as well as the potential mediation by visiting decisions. Data was collected via questionnaires administered to 154 tourists at TWA Angke Kapuk and analyzed using path analysis techniques. The findings revealed that both social media marketing and destination image significantly and positively influenced visiting decisions and tourist satisfaction. Moreover, the impact of social media marketing and destination image on tourist satisfaction was found to be greater when mediated by visiting decisions. Consequently, managers at TWA Angke Kapuk must enhance the utilization of various social media platforms and enrich content to bolster the positive perception of the destination.